2005
DOI: 10.1111/j.1365-2265.2005.02354.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor polymorphism (CAG repeats) and androgenicity

Abstract: Summary Objective  Polymorphism of the androgen receptor (AR) has been related to various pathophysiological conditions, such as osteoporosis and infertility. The objectives of this study were to evaluate the frequency of distribution in a normal Italian population and to assess CAG repeats (CAGr) in other conditions, such as hypoandrogenism, potentially influenced by AR polymorphism. Patients and measurements  CAGr polymorphism was determined in a group of 91 healthy normoandrogenized subjects, 29 hypoandroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 33 publications
6
42
0
6
Order By: Relevance
“…Apparent discrepancies between studies may be underlined by differences in population genetic background, and the age of enrolled men. There is one study in young men, which did not find significant association between testosterone levels and a number of CAG repeats (Canale et al 2005). These and our results suggest that the current testosterone levels are independent of androgen receptor sensitivity.…”
Section: Discussionsupporting
confidence: 49%
“…Apparent discrepancies between studies may be underlined by differences in population genetic background, and the age of enrolled men. There is one study in young men, which did not find significant association between testosterone levels and a number of CAG repeats (Canale et al 2005). These and our results suggest that the current testosterone levels are independent of androgen receptor sensitivity.…”
Section: Discussionsupporting
confidence: 49%
“…1), indicating that trinucleotide CAG repeat length might co-regulate the AR function, being different the distribution both between fertile and infertile male and even between the well-known forms of infertility and the idiopathic ones. These data can gain more weight if one considers that the range of our fertile participants was not different form those reported by other Italian Authors in previously published works [40][41][42]. Indeed, in a paper by Canale et al [42] the Authors showed a range of 18-26 CAG repeats with only one case with CAG repeat number >25 in the control group, while in another paper by Ferlin et al [41], the control group had a wide range of 9-30, event though the patients with CAG repeat number below 15 were only 3 % and those above 25 were less than 10 %.…”
Section: Discussionmentioning
confidence: 68%
“…These data can gain more weight if one considers that the range of our fertile participants was not different form those reported by other Italian Authors in previously published works [40][41][42]. Indeed, in a paper by Canale et al [42] the Authors showed a range of 18-26 CAG repeats with only one case with CAG repeat number >25 in the control group, while in another paper by Ferlin et al [41], the control group had a wide range of 9-30, event though the patients with CAG repeat number below 15 were only 3 % and those above 25 were less than 10 %. Finally, delli Muti et al [40] showed a range of 15-27 with only 3 % of subjects with trinucleotide CAG repeat number above 25 in their control group.…”
Section: Discussionmentioning
confidence: 68%
“…There is also an inverse correlation between CAG repeat length and androgenicity (e.g. [35]). Decreased repeat length is associated with increased production of prostate specific antigen and increased sperm count in adolescent males [36,37].…”
Section: Introductionmentioning
confidence: 99%